The expression and inheritance of stem strength in irrigation wheat - Van den Berg, Emile (University of the Free State, 2010)
The aim of this study was to determine the inheritance and environmental factors that regulate stem strength in irrigation wheat. The strength of the stem is defined by its length and as an index of the function of the pressure which it takes to break the stem, the pith thickness of the stem wall at breaking point and the length of the internodes. In the first experiment a set of parents was evaluated to determine the differences amongst parents for stem strength and its components. The parents significantly differed in stem length and strength. Some parental genotypes had shorter and more solid stems. For the second experiment the same parental genotypes were used to create a diallel set of progeny. The progeny and the parents were planted in pots in the tunnel in a replicated experiment to evaluate plant height and stem strength. It was found that the variances for all characteristics were significant, but the additive component (general combining ability) was higher than the dominance component. The parents differed significantly in their ability to produce F1 progeny with stronger stems. The calculated heritability was high and significant, which showed that the best way to select for improved stem strength is to select amongst plants in the progeny of the parents with the highest combining ability for the desirable traits. The third experiment was done to determine the interaction of higher plant density and higher N fertilisation on the expression of stem strength. This experiment (parents and progeny) was planted in pots in a tunnel. It was found that genotype, plant density and N fertilisation had a highly significant effect on stem strength. The ability of the parents to produce progeny with strong stems differed. The parents with the solid stem phenotype and shorter stems generally produced progeny with stronger stems. The variance for general combining ability (additive genetic variance) is significant. The heritability for all characteristics was high, but higher in increased plant density or increased nitrogen application but with the highest expression where both plant density and nitrogen application were increased. This indicates that selection for stem strength should be more successful in populations with a higher plant density under high N conditions.

Die studie is onderneem om die oorerflikheid van stamsterkte en die eienskappe wat dit bepaal by verskillende omgewingstoestande, te ondersoek. Die sterkte van die stam is gedefinieer as die lengte daarvan, en word weergegee in terme van `n indeks wat `n funksie is van die krag wat benodig word om die stam te breek, die kerndikte van die stam by breekpunt en die litlengte. In die eerste eksperiment is `n stel ouers ondersoek om die verskille tussen ouers vir die stamsterkte en die komponente daarvan te meet. Daar is gevind dat die ouers betekenisvol in lengte en die sterkte van die stam verskil. Hierdie ouer genotipes het `n soliede en korter stam. In die tweede eksperiment is `n dialeel stel kruisings van hierdie ouers gegenereer. Die kruisings, sowel as die ouerlyne, is in `n eksperiment met herhalings in potte geplant in `n tonnel en vir planthoogte en stamsterkte geëvalueer. Daar is gevind dat die variasie vir alle eienskappe betekenisvol is, maar dat die additiewe (algemene kombineringsvermoë) komponent heelwat hoër is. Ouers het betekenisvol van mekaar verskil in hul vermoë om F1 nageslag met sterk strooi te produseer. Die oorerflikheid was hoog en betekenisvol, wat aandui dat die aangewese manier om stamsterkte te verbeter, sou berus tussen plante binne die nageslag van ouers met die beste kombineervermoë vir die eienskap. Die derde eksperiment is uitgevoer om te bepaal wat die interaksie van verhoogde plantestand en verhoogde stikstofbemesting op die uitdrukking van stamsterkte is. Die eksperiment (ouers sowel as hul nageslag) is in potte in `n tonnel aangeplant. Daar is gevind dat die drie hoofkomponente naamlik genotipe, stand en stikstofbemesting `n hoogs betekenisvolle effek op stamsterkte gehad het. Die ouers het verskil in hul vermoë om nageslag te lewer met sterk stamme. Die ouers met die soliede stam fenotipe en korter strooi het deurgaans `n nageslag gelewer met sterker stamme. Die variansie vir algemene kombineervermoë (additiewe genetiese variasie) was betekenisvol. Die berekende oorerflikheid was vir alle eienskappe hoog, maar hoër by `n verhoogde plantestand of verhoogde stikstofbemesting met die hoogste uitdrukking waar beide plantestand en stikstoftoediening verhoog is. Dit beklemtoon `n strategie waar seleksie vir stamsterkte beloof om meer suksesvol te wees in populasies wat aan `n hoër stand en hoër stikstofbemesting onderwerp is.
Dissertation (M.Sc.Agric. (Plant Sciences (Plant Breeding))--University of the Free State, 2008
Keywords: Wheat -- Breeding -- South Africa; Lodging of grain -- South Africa; Stems (Botany)